Lipid profile and nutritional status of a pediatric population with sickle cell anemia: differences between gender and association with severity markers (Research, Society and Development, 2021)
Objective: To investigate the associations between nutritional status and lipid profile with biomarkers of hemolysis and inflammation in sickle cell anemia, in addition to considering gender differences. Methods: This cross-sectional study analyzed nutritional, and biochemical data of pediatric patients carrying sickle cell anemia. Results: Vitamin A, apolipoprotein B, total cholesterol, low-density lipoprotein, and non-high-density lipoprotein cholesterol were lower in boys. Hemoglobin was significantly lower, and the white blood cells and lactate dehydrogenase were higher in boys. Body mass index, vitamin A, and triglycerides were associated with hemoglobin levels, while apolipoprotein A-I was associated with white blood cells and total bilirubin. Additionally, body mass index and vitamin A were associated with lactate dehydrogenase. Vitamin A showed significant predictive power in hemoglobin alteration and lactate dehydrogenase, while apolipoprotein A-I was able to predict high white blood cells values and total bilirubin. Conclusion: This study found in a pediatric population with sickle cell anemia that body mass index, vitamin A, triglycerides, and apolipoprotein A-I were associated with biomarkers of hemolysis and inflammation. Boys exhibited the greater nutritional deficit and severity of the disease.